Productive and reproductive performances of buffaloes in Bhola district of Bangladesh - Jahan, I; Sarker, N; Alam, S; Rahman, M K; Alam, M K; Khandakar, M M H; Bari, M S; Habib, M R; Islam, M A (Bangladesh Journal of Animal Science, 2024)
This study aimed to evaluate the productive and reproductive performance of buffaloes across five sub-districts (Burhanuddin, Lalmohan, Char Fasson, Bhola Sadar, and Tazumuddin) in the Bhola district of Bangladesh. A face-to-face survey was conducted with 309 buffalo farmers. Daily milk yield ranged from 1.2 to 4.3 liters/cow/day, with over 90% of farmers selling to Goalas (local milk collectors) at BDT 87±22/liter. Lower milk prices were often reported due to pre-arranged advance loans from milkmen. Significant difference (p < 0.05) was observed in milk yield across lactation stages, with the highest yields (2.9–3.9 L/day/buffalo) during the first 90 days. Most farmers (82%) relied solely on grazing in the Bathan system, without supplemental concentrate feed. Reproductive parameters showed significant variation (p < 0.05) across the sub-districts, with Lalmohan having the lowest age at sexual maturity (2.98±0.08 years) and the shortest postpartum heat period (57.1±13.62 days). Bhola Sadar had the shortest calving intervals (11.92±0.43 months) and gestation periods (297.10±6.97 days). Burhanuddin had the lowest number of services per conception (1.46±0.50). To improve buffalo farming outcomes, it is decisive to establish local cooperatives for fair milk pricing, introduce supplemental feeding, enhance access to breeding resources, and bolster financial support, educational programs, and infrastructure. Bangladesh Journal of Animal Science 53(3): 111-120, 2024